EFFECT OF Gliricidia sepium LEAVES EXTRACTS ON Aedes aegypti: LARVICIDAL ACTIVITY - K.V., Krishnaveni; R., ThaiyalNayaki; M*., Balasubramanian, G (Journal of Phytology, 2015)
Mosquitoes are the single most important group of insects in terms of public health significance and causing diseases. They are the vectors for the transmission of many viral pathogens and pose serious threat to human health. Chemical insecticides are widely used but they are non-selective and harmful to beneficial organisms. In the present study G. Sepium leaves extracts were used to analyse its effect against Aedes aegypti, to compare the mortality rate while using different solvent extracts of the leaf, to identify the solvent extract which give high rate of larval mortality and to characterise the compounds present in the corresponding leaf extract using phytochemical analysis. The ethanolic extract of G. sepium leaves constitute flavanoids, steroids, glycoside, carbohydrate and saponins compound. Thus it was found to have an inhibitory effect on the growth of larvae than other solvent extracts. In the statistical analysis highest significant difference was observed between 1.5g/l and 2.0g/l concentration of ethanolic extract and other extracts. However no significant difference was observed in other concentrations. The larvicidal activity of the plant extract may be attributed to the presence of active compounds like terpinoids, saponins and steroids.